2016
DOI: 10.3109/01902148.2016.1143537
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human deoxyribonuclease therapy improves airway resistance and reduces DNA extracellular traps in a murine acute asthma model

Abstract: Our results suggest that extracellular DNA in mucus play a role in lower airways obstruction in OVA asthma protocol and that the treatment with rhDNase improved lung function and DNA extracellular traps, with no direct cellular anti-inflammatory effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 25 publications
5
33
0
Order By: Relevance
“…This treatment reduces the risk of disease exacerbation and improves overall outcome for the patient ( 98 100 ). Consistent with those findings, DNase treatment and removal of NETs has also been shown to improve lung function in murine asthma models ( 101 ).…”
Section: Nets and Diseasesupporting
confidence: 64%
“…This treatment reduces the risk of disease exacerbation and improves overall outcome for the patient ( 98 100 ). Consistent with those findings, DNase treatment and removal of NETs has also been shown to improve lung function in murine asthma models ( 101 ).…”
Section: Nets and Diseasesupporting
confidence: 64%
“…A subgroup of patients expressed a high level of neutrophils and NETs, in which the extracellular mtDNA was associated with NE 97 . In an animal model of asthma, the treatment with deoxyribonuclease, which cleaves extracellular DNA, resulted in an improvement of airway resistance and abolished extracellular DNA content in BALF as well as goblet cell hyperplasia 98 . Peripheral blood eosinophils from patients with severe eosinophilic asthma (SEA) may be more activated to produce EETs than those from patients with nonsevere asthma (NSA), which further induces inflammation in asthmatic airways 99 .…”
Section: Eets In Asthma and Rhinosinusitismentioning
confidence: 99%
“…[42] Currently, asthma can be divided into four distinct phenotypes termed eosinophilic, neutrophilic, mixed granulocytic, and pauci-granulocytic phenotypes by investigating granulocyte infiltration in induced sputum. [43] Although the majority of patients with eosinophilic asthma are sensitive to corticosteroids, there is recognition that some asthmatics, particularly those who have severe disease and are resistant to corticosteroids, have elevated neutrophil counts in their airways.…”
Section: Neutrophil Extracellular Traps and Asthmamentioning
confidence: 99%
“…[53] demonstrated that CF patients treated with DNase resulted in an increasing in NE activity and subsequent injury to the lung tissue. In a mouse model of asthma,[42] it was observed that extracellular DNA in mucous was involved in lower airway obstruction in an ovalbumin-induced model of asthma. In particular, lung functionally was improved by means of treatment with an intranasal administration of recombinant human DNase.…”
Section: Neutrophil Extracellular Traps and Asthmamentioning
confidence: 99%
See 1 more Smart Citation